The gift of the magi - Wurfel, Marlene (My University, 2018)
A retelling of a classic 1905 story by O. Henry, an American short story writer well known for his surprise endings. This holiday story has been adapted for younger audiences and is sometimes called The Watch and The Comb story.
Keywords: storytelling; children's stories